The Effect of Task-Based Writing Instruction on Iranian Pre-Intermediate EFL Learners’ Self-Efficacy and Epistemic Beliefs - Nooshin Iravani (Educational Considerations, 2023)
Generally, writing—and second-language (L2) writing in particular—causes a lot of challenges. Indeed, many L2 students who are very proficient in speaking and reading may encounter many difficulties while composing a letter or a biography. They suffer from a low level of self-efficacy and confidence in this respect. Therefore, this research was aimed at shedding light on the effects of task-based writing instruction on improving English as a Foreign Language (EFL) learners' self-efficacy and epistemic beliefs associated with writing skills. To this end, a sample of 36 Iranian male and female pre-intermediate learners took part in this research. They formed two groups: experimental and control. The participants in the experimental group took part in 18 intensive writing sessions which were held three times a week. In each session, the teacher and students collaborated to write a text. They took part in carrying out some writing tasks in which they cooperated to write. This was followed by two interviews with different sets of questions conducted with four participants, as representatives of all students, in the second and sixth weeks of the study. The data were also collected using two interviews, the writing self-efficacy scale, and the Epistemological Beliefs Survey. The results showed the positive effect of task-based writing instruction concerning writing skills, self-efficacy, and epistemic beliefs. This study has implications for educators who can use this method to develop EFL learners’ self-efficacy and epistemic beliefs, which, in turn, can enhance their writing skills as well.
Keywords: EFL learners; Epistemic beliefs; Self-efficacy; Task-based writing instruction